A new species of the genus Alsodes (Anura: Neobatrachia) from the Nothofagus forest, Coastal Range, Southern Chile, identified by its karyotype - P., César C. Cuevas (Zootaxa, 2008)
Based on morphology, distribution, and on the presence of a novel diploid number (2n = 30 chromosomes), a new species of frog Alsodes norae from the Coastal Range, Valdivia Province temperate Nothofagus forest, Southern Chile, is described. Hypothetical chromosomal rearrangements and the origin of its unusual karyotype are discussed. Among the South American frogs, the genus Alsodes is recognized by its complex relationships, and based on karyological and geographical distribution information its species are grouped in two larger groups, herein: the Andean group which is conservative, and the Coastal group which is far more variable in gross chromosome morphology. Additionally, the inclusion of Alsodes in the new family Cycloramphidae is commented.